Disambiguation of novel labels and referential facts: A developmental perspective. Issue 2 (April 2014) - Kalashnikova, Marina; Mattock, Karen; Monaghan, Padraic
Disambiguation refers to children's tendency to assign novel labels to unfamiliar rather than familiar referents. It is employed as a word-learning strategy, but it remains unknown whether it is a domain-specific phenomenon or a manifestation of more general pragmatic competence. To assess the domain-specificity and development of disambiguation, this study tested children from two age groups (ages 3;7–4;6 and 4;7–5;7) and adults on a disambiguation of novel labels and referential facts paradigm. A linear contrast analysis showed that the difference between disambiguation from labels and disambiguation from facts increased significantly as the participants' age increased. The results indicate that at the early stages of word learning, children reason by exclusion to disambiguate the meaning of a variety of referential actions, but with increasing understanding about the communicative process, this inferential reasoning develops into a strategy limited to lexical acquisition.